Surviving COVID-19 and Battling Fibrosis: A Retrospective Cohort Study Across Three Pandemic Waves - Mihai Lazar; Ecaterina Constanta Barbu; Cristina Emilia Chitu; Mihaela Buzoianu; Andreea Catalina Petre; Catalin Tiliscan; Stefan Sorin Arama; Victoria Arama; Daniela Adriana Ion; Mihaela Cristina Olariu (Diagnostics)
Background/Objectives: We aimed to characterize the fibrosis following COVID-19 pneumonia, using quantitative analysis, after three months and subsequently, after two years of patients’ release from the hospital, and to identify the risk factors for pulmonary fibrosis. Methods: We performed a retrospective, observational cohort study on 420 patients with severe forms of COVID-19. For all patients, we registered demographic, inflammatory and biochemical parameters, complete blood count and D-dimers; all patients underwent three computed tomography scans (at admittance, at 3 months and at 2 years). Results: We found fibrosis in 67.9% of patients at the 3-month evaluation and in 42.4% of patients at the 2-year evaluation, registering a significant decrease in the severe and moderate fibrosis cases, with a slight increase in the mild fibrosis cases. The risk of fibrosis was found to be proportional to the values of age, duration of hospital stay, inflammatory markers (ESR, fibrinogen), cytolytic markers (LDH, AST) and D-dimers. The highest correlations with lung fibrosis were registered for interstitial pulmonary involvement (for the 3-month evaluation) and total pulmonary involvement (for the 2-year evaluation). Conclusions: Lung fibrosis represents a significant post-COVID-19 complication found in 42% of patients with severe forms of pneumonia at the 2-year evaluation. A significant overall decrease in the severity of lung fibrosis was registered at the 2-year evaluation compared to the 3-month evaluation. We consider that the amount of interstitial pulmonary involvement represents the optimal parameter to estimate the risk of lung fibrosis following SARS-CoV-2 pneumonia.